Analisis Pengendalian Persediaan Menggunakan Metode Economic Order Quantity (EOQ) Guna Optimalisasi Persediaan Bahan Baku - Agustina, Rizka; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This research aims to analyze inventory using the economic order quantity method in order to optimize the supply of soybean raw materials at the Tempe Bd 6 Industrial House, Kec.Trimurjo. The research method used is a quantitative descriptive method. The object of this research is Tempe Industrial House Bd 6. The types of data in this research are quantitative data and qualitative data, while the data sources used in this research are primary data and secondary data. The data collection techniques used are observation, interviews/interviews and documentation. The research uses the economic order quantity (EOQ) method to optimize raw material supplies. The results of this research show that the economic order quantity method is more optimal in controlling raw material supplies compared to the conventional method applied by Rumah Industri Tempe Bd 6, so that inventory control using the economic order quantity method can reduce ordering costs and storage costs and minimize the occurrence of stock outs.